OCULAR COMPLICATIONS OF LEPROSY - Castilho-Palitot, Aganeide; Diniz, Alcides da Silva; Lynch Gaete, Maria Isabel; Ximenes, Ricardo Arraes de Alencar (Revista de Ciências da Saúde Nova Esperança, 2017)
Leprosy still constitutes a public health problem due to ocular complications. To expose the ocular complications of leprosy, through integrative review, contributing to practice objectivity to help changing attitudes of health professionals in relation to leprosy patients, according to the World Health Organization Vision 2020 Program. The authors conducted a critical integrative review employing inclusion criteria: the research has been published between 1930 and 2013 and be restricted to ocular complications of leprosy, been provided the inclusion of other aspects relate to the disease. Without limiting the search to English language, one employed the descriptors [leprosy], [eye], [ocular], [Hansen’s disease], [Mycobacterium leprae] associated to [sequela], [complications] e [deformity], linked by Boolean connectors AND/OR, applied to MedLine, SCIELO, Lilacs, Scopus. EBSCO, Cochrane and Google Scholar database, using the program JabRef®, version 2.9.2. We found 387 publications, 33 of which were part of the review. Among the ocular complications, lagophthalmos, cataract, uveitis, blindness and iris changes were most frequent, with variable prevalence according to patient age, disease duration, place of study and level of detail of the eye examination. There was consensus that the prevalence of ocular complications can be reduced with the introduction of ophthalmic examination from diagnosis and after completion of multidrug therapy. Ocular complications are still worrying thus health professionals should refer these patients to ophthalmologic exam.